IMPLEMENTASI KEBIJAKAN STANDAR DOSEN PADA PROGRAM STUDI ADMINISTRASI BISNIS POLITEKNIK INFORMATIKA NASIONAL - Nasir, Nasir (Mimbar Administrasi Mandiri, 2024)
The lecturer has important role in education system. Lecturers play an important role in the teaching and learning process, therefore to improve the quality of higher education lecturers play an important role in the education process, especially in universities. This reserach used Descriptive Qualitative method. This method is relevant, because this research was a descriptive to describe and observe an implementation of lecturer policy standard at Administration Business Program In Polythecnic of National Informatics. Data analysis method were Data Collection,  data reduction, display data, verification, data interpretation, and conclusion. The result showed that generally the lecturer policy standard at Administration Business Program In Polythecnic of National Informatics is not maximal. The result based on the obideience step approach, the smooth implementation of routine function and an intended impact realization approach by Repley and Grace A. Franklin faced some obstacles. The obstacles are some lecturers do not have academik position, lecturer ration and student are not complete, and also the lecturers do not active for doing research and dedication to the society.